Triterpene Production in Centella Asiatica (L.) Urban (Pegaga) Callus and Cell Suspension Cultures - Ling, Anna Pick Kiong (2004)
Centella asiatica or locally known as ‘Pegaga’ is one of the most common medicinal plants used by diverse ancient cultures and tribal groups. Its medicinal values are mainly attributed to the presence of the triterpene constituents. As there is still no information available on the triterpene production in cultured tissues, studies were carried out in determining the triterpene distribution particularly asiatic acid, madecassic acid, asiaticoside and madecassoside in intact plants of the twelve accessions of C. asiatica collected throughout Malaysia as well as in the callus and cell suspension cultures. Results obtained from the studies revealed that twelve accessions of C. asiatica differed both in their morphologies and their triterpene contents. The triterpenes constituents were detected at a range of 0.134 to 1.655 mg/g dry weight in the whole plant intact tissues. Triterpenes were also successfully detected in the callus (0.014 to 0.773 mg/g dry weight) and cell suspension cultures (0.005 to 0.084 mg/g dry weight), the amount that were lower than that produced in the intact tissues. However, manipulating the physical culture conditions, feeding of precursor, elicitation as well as amino acid addition managed to increase the triterpenes content in cultured tissues. Studies on the effects of the medium composition show that full strength of the basal Murashige and Skoog medium supplemented with B5 vitamins and sucrose (3-4%) increased the triterpenes content in both callus and cell suspension cultures. An interaction of auxincytokinin has observed being important for both callus and cell suspension cultures in enhancing triterpenes production. Higher triterpenes content was obtained in callus treated with 2,4-D and kinetin while the combination of kinetin and dicamba enhanced the triterpenes production in cell suspension cultures. The precursor-feeding studies revealed that lower concentrations of squalene (0.16 mg/L in callus and 0.8 mg/L in cells) were preferred for triterpenes production. Squalene at 0.16 mg/L had successfully triggered the production of madecassoside, asiaticoside and madecassic acid in callus cultures while asiatic acid and madecassic acid content was increased in cells treated with 0.8 mg/L squalene. The elicitor studies exhibited that the different elicitors showed distinctive effects on triterpenes production. Nevertheless, supplementation of succinic acid at 3 and 4 mg/L was found the best in increasing the triterpenes production in callus and cell suspension cultures, respectively. Addition of amino acid into the culture media was also found to promote the triterpenes production in in vitro cultures. The study further concluded that the combinations of the optimized factors namely medium composition, precursor feeding, elicitation and amino acid addition is a very useful strategy in enhancing the triterpenes production particularly the asiatic acid and madecassic acid in in vitro cultures of C. asiatica.